First Experience Using a New Minimally Invasive Screw–Rod System for Completely Percutaneous Pedicle Screw Fixation of the Cervical Spine - Scholz, Christoph; Hohenhaus, Marc; Hubbe, Ulrich; Volz, Florian; Watzlawick, Ralf; Beck, Jürgen; Klingler, Jan-Helge (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
In contrast to the thoracolumbar spine, where pedicle screws can be inserted via a minimally invasive, percutaneous technique through small skin incisions, all previously available cervical instrumentation systems required a larger midline incision, especially for rod insertion. Screw placement via small incisions reduces the risk of wound healing disorders and blood loss, and patients can be mobilized more quickly and with less pain. In 2022, a cervical, minimally invasive stabilization system became available for the complete percutaneous insertion of both cervical pedicle screws and rods. We report on the first results and experiences with this new technology.In this retrospective case series, we included patients with cervical instability treated by minimally invasive percutaneous cervical and upper thoracic spine pedicle screw and rod insertion between August 2022 and August 2023. Intra- and postoperative complications as well as revision surgeries were recorded. The screw position was evaluated by three examiners in the postoperative computed tomography (CT) using the Bredow classification.Our series includes six male patients (age = 56.9 ± 12.9 years; body mass index [BMI] = 29.8 ± 9.6 kg/m2). The indication for surgery was trauma, tumor, and degenerative stenosis in two patients each. An excellent/good screw position (Bredow 1 and 2) was found in 84.4% of the screws (n = 27/32). None of the screws rated as Bredow 3 (n = 2/32) or Bredow 4 (n = 3/32) resulted in a neurological deficit or radicular pain and none had to be repositioned. No neurologic complication or revision surgery occurred. As a complication not directly related to the surgery technique, one patient died of a pulmonary lung embolism on the seventh postoperative day.The results of this study indicate that minimally invasive percutaneous implantation of a pedicle screw–rod system is also possible in the cervical spine with sufficient accuracy using intraoperative navigation. However, technical details, possible pitfalls and finally careful patient selection must be taken into account.
Keywords: cervical spine; minimally invasive; navigation; pedicle screws; spinal instability